The Effect of Wordwall-Based Learning Media on Fourth Grade Students' Motivation in Social Studies Learning at Elementary School - Azmi M , Nur; Suardi, Suardi; Idawati, Idawati (FKIP - Universitas Riau, 2025)
This study aims to investigate the effect of Wordwall-based learning media on students' motivation in Social Studies among fourth-grade students at Gugus II Elementary Schools, Biringkanaya District, Makassar City. The study employed a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The research sample consisted of 41 students, with 20 students in the experimental class receiving instruction via Wordwall-based media, and 21 students in the control class undergoing traditional teaching methods. Students' motivational data were collected using closed questionnaires and analyzed using an Independent Samples T-Test in the JASP statistical software. The results indicated that the use of Wordwall-based learning media significantly increased students' learning motivation, demonstrated by a p-value of less than 0.001. These findings imply that educators should integrate technology-based instructional media to enhance student motivation and engagement in Social Studies learning.